More crops with less water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Crops can be grown without fertilizers and even without soil, but they cannot survive without water. Without adequate moisture plants cannot mobilize soil nutrients and Jack of water at crucial stages of development will leave plant growth stunted....